2021
DOI: 10.3389/fphar.2021.763853
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ2 Pro12Ala Polymorphism is Associated in Children With Traits Related to Susceptibility to Type 2 Diabetes

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a ligand-activated nuclear receptor that regulates glucose and lipid metabolism. Pharmacological activators of PPARγ are being used as a treatment of obesity related disorders such as dyslipidaemia and type 2 diabetes, but questions remain open regarding the effects of PPARγ on traits related to the development of type 2 diabetes. In our study, we have analyzed the relationship of the common variant Pro12Ala in the human PPARγ2 gene with the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…This suggested that expression of the VEGF gene may be one of the common genetic bases between IR and DR. Pro12Ala is located at the amino-terminus of the PPAR-γ 2 gene and was found to be associated with higher insulin sensitivity ( 59 ). Pro12Ala mutations may affect lipid metabolism, and pancreatic β-cell function, and be associated with the risk of IR ( 60 ). Meanwhile, it was also found that the alanine variant of Pro12Ala may be associated with a lower risk of DR ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that expression of the VEGF gene may be one of the common genetic bases between IR and DR. Pro12Ala is located at the amino-terminus of the PPAR-γ 2 gene and was found to be associated with higher insulin sensitivity ( 59 ). Pro12Ala mutations may affect lipid metabolism, and pancreatic β-cell function, and be associated with the risk of IR ( 60 ). Meanwhile, it was also found that the alanine variant of Pro12Ala may be associated with a lower risk of DR ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, FTO is an important gene in obesity pathogenesis due to its ability to modulate food intake and satiety perception; however, these modulations are often linked to a genetic polymorphism ( 57 ) rather than to gene expression. This consideration could be extended to other genes such as PPARγ ( 58 ). Since genetic polymorphisms can influence gene expression, another limitation related to this point is that we haven’t analyzed the genetic background of the population enrolled in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Одна из его изоформ -PPARγ кодируетcя геном PPARG. В медицинской практике полиморфизм Pro12Ala гена PPARG связывают с предрасположенностью к увеличению массы тела, накоплению жировой ткани, риском развития сахарного диабета II типа и атеросклероза [13]. В настоящее время описывают гораздо более широкие регуляторные роли PPAR.…”
Section: оригинальные исследования Original Researchunclassified